The effects of plyometric versus dynamic stabilization and balance training on lower extremity biomechanics - Myer, G. D.; Ford, K. R.; McLean, S. G.; Hewett, T. E. (The American Journal of Sports Medicine, 2006)
Background: Neuromuscular training that includes both plyometric and dynamic stabilization/balance exercises alters movement biomechanics and reduces ACL injury risk in female athletes. The biomechanical effects of plyometric and balance training utilized separately are unknown.